Geometry of Former Subglacial Water Channels and Cavities - Walder, Joseph; Hallet, Bernard (Journal of Glaciology, 1979)
Abstract The spatial pattern of the formerly active processes of water flow, cavitation, abrasion, dissolution, and precipitation at the base of a small cirque glacier has been reconstructed by detailed mapping of surficial features on recently deglaciated limestone bedrock near the glacier terminus. Our interpretation of these features, which reflect basal conditions averaged over a period of several or several tens of years, leads us to the following conclusions: 1. A nearly continuous, non-arborescent network of cavities and incised channels existed and probably acted as the primary drainage of melt waters. This network evolved through time as many channels were filled, perhaps intermittently, by basal ice. 2. At least 20% of the glacier sole was separated from the bed by water-filled cavities. The rest of the glacier–rock interface characteristically comprises a very thin water film. 3. Abrasion was locally intensified, relative to chemical alteration, in 5–10 m wide zones paralleling the ice-flow direction, perhaps as a result of locally enhanced sheet flow of subglacial water.